Penerapan Discovery Learning Berbantuan PowerPoint dalam Pembelajaran Biologi Materi Jaringan Hewan - Laya Rhahillia; Dian Rahmawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The application of innovative learning methods is essential. One method that attracts attention is Discovery Learning. Along with advances in technology, the integration of learning aids such as Power Point has become an important aspect in supporting the teaching process. This research aims to obtain results from the implementation of PPT-assisted Discovery Learning on animal tissue material at SMA Negeri 1 Pamarayan. This research was conducted in September-October 2023 at SMA Negeri 1 Pamarayan with research subjects totaling 41 students. The implementation system consists of four stages, namely: planning, action, observation and reflection. The research results show that this model is a powerful instrument in efforts to improve student learning outcomes in the field of biology, as can be seen from the improvement in student learning outcomes. The use of the Discovery Learning model supported by PowerPoint media can increase student learning motivation. Visualization of abstract concepts through Power Point makes complex animal tissue material easier to understand and interesting, thus triggering students' curiosity and enthusiasm for learning. This increase in results occurred due to the influence of the discovery learning model which requires students to be able to obtain their own knowledge and information. Apart from that, students are required to play an active role in the learning process so that it becomes easier for students to accept learning, so that students' learning achievement increases.